The Role of Pesantren Leaders in the Digital Age - Zulkarnain, Lutfi (Indo Consultan Energi, 2023)
Pesantren leaders must be able to play an active role in responding to speedy technological developments in today's digital era so that pesantren can produce students who are not only technologically literate and have intellectual intelligence but also social piety and spiritual stability. This article aims to provide an overview of the role of pesantren leaders in facing the digital era. The method used in writing this article is the literature method with a descriptive analysis approach. The results of the study show that the role of pesantren leaders in the digital era can be demonstrated through the leadership's ability to oversee change and the use of technology that is developing rapidly at this time by revitalizing the curriculum, providing supporting infrastructure, providing training on matters related to digitalization to teachers and students to improve the competence of teachers and students related to technological developments, as well as actively communicate with parents and the government to get moral and material support so that pesantren can keep up with technological advances in the current digital era but can also maintain the traditions of the pesantren itself.